Pengaruh Pengetahuan Dan Dukungan Keluarga Terhadap Kepatuhan Berobat Pada Pasien Tuberkulosis Paru Di RSUD Dr. Soeroto, Kabupaten Ngawi - Husna, Happy Bunga Isyraqul; Abidin, Zaenal; Ramadhanintyas, Karina Nur (Universitas Tribhuwana Tunggadewi, 2024)
Pulmonary tuberculosis (TB) is the number one deadly infectious disease in the world caused by the bacterium Mycobacterium tuberculosis. Indonesia ranks third globally, and East Java ranks second in Indonesia. Secondary data from Dr. Soeroto Ngawi Regional Hospital in 2022 indicate that there will be 15 patients resistant to drugs. The research aims to determine the influence of knowledge and family support on medication adherence among tuberculosis patients at Dr. Soeroto Ngawi Regional Hospital. The research design is quantitative observational with a cross-sectional approach. The study population consists of all pulmonary TB patients aged ≥ 12 years recorded from January to July 2022 at Dr. Soeroto Ngawi Regional Hospital, with a selected sample of 48 respondents using simple random sampling probability techniques. Research instruments include direct observation, interviews, and questionnaires. The research period was from December 4, 2022, to April 9, 2023. The results showed that the majority of pulmonary tuberculosis patients are female, aged between 26 and 45 years, with educational levels ranging from junior high school to high school. Most respondents have good knowledge (56.2%) and good family support (60.4%). The analysis indicates that there is an influence of knowledge factors and family support factors on medication adherence in pulmonary tuberculosis patients. The most dominant factor affecting medication adherence in pulmonary tuberculosis patients is family support.